2006
DOI: 10.1007/s00417-006-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional optical coherence tomographic findings in central serous chorioretinopathy

Abstract: OCT-ophthalmoscope detects morphologic changes easily and noninvasively at the point of dye leakage in eyes with CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 15 publications
(20 reference statements)
1
45
1
4
Order By: Relevance
“…However, PED prevalence may vary from 8% to 71% [11,18,19,22]. In our study, OCT did not show any PED in female cases.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, PED prevalence may vary from 8% to 71% [11,18,19,22]. In our study, OCT did not show any PED in female cases.…”
Section: Discussioncontrasting
confidence: 60%
“…The most common spectral domain OCT findings detected in the patients with acute CSCR are PED, RPE bulging, SMD, dipping pattern, brush-border pattern or elongation of photoreceptor outer segments and IHRDs or SHRDs [2,13,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…FFA shows a focal RPE leak with pooling of the dye in the overlying serous retinal detachment. 4 The morphological alterations occurring at the site of focal leak have been studied and reported to show RPE abnormalities including an RPE bulge in the posterior pole, 9 RPE detachments, 9-13 reproducible small RPE bulge (which researchers did not consider to be PEDs or artifactual), 11 irregular lesions of RPE, 14 and more recently, RPE disruption indicating an anatomical microrip of RPE. shows PED as a complete ring (thick arrow) and retinal pigment epithelium breech corresponding to the point of leak (thin arrow) (top left).…”
Section: Discussionmentioning
confidence: 99%
“…However, this treatment is controversial, because comparable visual outcomes are normally achieved over time with no intervention and no risks of adverse effects [31,32]. Recent studies in eyes with chronic CSC have demonstrated a spatial correlation between the ALS at fluorescein angiography and RPE alterations on optical coherence tomography (OCT) [33][34][35]. This observation suggests that persistent leak and sub-retinal fluid can lead to permanent RPE changes, which cause irreversible visual loss [36].…”
Section: Discussionmentioning
confidence: 96%